THE EFFECT OF THE TOTAL UNDERGRADUATE STUDENTS, POSTGRADUATE STUDENTS, INTERNATIONAL STUDENTS, LECTURERS, AND INTERNATIONAL LECTURERS ON SUSTAINABILITY REPORT (Empirical Study on Asian Universities Registered in UI GreenMetric 2025) - Arifah Nur Kamila; Surya Raharja (Diponegoro Journal of Accounting, 2026)
This study aims to determine the effect of the total undergraduate students, postgraduate students, international students, lecturers, and international lecturers on sustainability report at Asian universities listed in UI GreenMetric. The dependent variable in this study uses the Overall Score in UI GreenMetric. Meanwhile, the independent variables in this study are the of total undergraduate students, postgraduate students, international students, lecturers, and international lecturers.The data used in this study is secondary data obtained from the UI GreenMetric World University Rankings and Quacquarelli Symonds (QS) World University Rankings websites. The final sample size used was 152 Asian universities in 2025. The sampling technique used was purposive sampling. The data analysis method in this study used multiple linear regression analysis.The results of the study provide evidence that the total of postgraduate students and lecturers has a positive and significant effect on sustainability report, thus accepting the hypothesis. Meanwhile, the variables of the total of undergraduate students, international students, and international lecturers do not have significant effect on sustainability report.